Anchoring of FRET Sensors—A Requirement for Spatiotemporal Resolution - Ivanova, Elena V. (Sensors (Basel), 2016)
FRET biosensors have become a routine tool for investigating mechanisms and components of cell signaling. Strategies for improving them for particular applications are continuously sought. One important aspect to consider when designing FRET probes is the dynamic distribution and propagation of signals within living cells. We have addressed this issue by directly comparing an anchored (taFS) to a non-anchored (naFS) cleavable FRET sensor. We chose a microtubule-associated protein tau as an anchor, as microtubules are abundant throughout the cytosol of cells. We show that tau-anchored FRET sensors are concentrated at the cytoskeleton and enriched in the neurite-like processes of cells, providing high intensity of the total signal. In addition, anchoring limits the diffusion of the sensor, enabling spatiotemporally resolved monitoring of subcellular variations in enzyme activity. Thus, anchoring is an important aspect to consider when designing FRET sensors for deeper understanding of cell signaling.